Prymas polski arcybiskup Antoni Kazimierz Ostrowski i jego troska o archidiecezję gnieźnieńską w czasie pobytu za granicą (1782-1784) w świetle korespondencji z kapitułą metropolitalną w Gnieźnie - Staniszewski, Paweł (Archiwa, Biblioteki i Muzea Kościelne, 2008)
Archbishop Antoni Kazimierz Ostrowski was the primate of Poland in the years 1777-1784. In older historiography Ostrowski was praised for his deep inner life, ascetical practices, exemplary life, works of mercy, approachability and hospitality. However, some new investigations put in doubt his exemplary priestly conduct. Primate Ostrowski who was sick then spent last two years of his life (1782-1784) abroad where he underwent medical treatment. We have a large correspondence from this period between the primate and the cathedral chapter of Gniezno. The author of the article analyzes these correspondences and clearly shows that archbishop Ostrowski, even when abroad, he really cared for his archdiocese’s affairs. Among his particular interest were the construction of a new seminary building, the renovation of the metropolitan cathedral of Gniezno and the expanding of the Primate’s palace in Warsaw. The article wants to prove that – despite numerous opinions about the Primate’s weaknesses – till the end of his life he strove to be a good shepherd, doing a lot of good things for his archdiocese and for the Church.